Guided wave optics and photonic devices - Ghatak, A. K. (Ajoy K.), 1939-; Bhadra, Shyamal (Optics and photonics (Boca Raton, Fla.), 2013)
Guided Wave Optics and Photonic Devices introduces readers to a broad cross-section of topics in this area, from the basics of guided wave optics and nonlinear optics to biophotonics. The book is inspired by and expands on lectures delivered by distinguished speakers at a three-week school on guided wave optics and devices organized at the CSIR-Central Glass and Ceramic Research Institute in Kolkata in 2011. An Introduction to Guided Wave Optics and Photonic Devices: Principles, Applications, and Future Directions The book discusses the concept of modes in a guided medium from first principles.